2005
DOI: 10.1097/00001756-200501190-00017
|View full text |Cite
|
Sign up to set email alerts
|

MRI diffusion coefficients in spinal cord correlate with axon morphometry

Abstract: Following spinal cord injury, diffusion MRI (DWI) has been shown to detect injury and functionally significant neuroprotection following treatment that otherwise would go undetected with conventional MRI. The underlying histologic correlates to directional apparent diffusion coefficients (ADC) obtained with DWI have not been determined, however, and we address this issue by directly correlating ADC values with corresponding axon morphometry in the normal rat cervical spinal cord. ADC values transverse (perpend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 14 publications
9
118
1
2
Order By: Relevance
“…Further, parallel ADC was found to be positively correlated with axonal diameter, and negatively with axonal number (Schwartz et al, 2005). It should be noted that other tissue parameters, such as axon density and tortuosity, crossing fibres and tract geometry may also contribute to differences in λ⊥ and λ || (Beaulieu, 2009;Schwartz et al, 2005). Whatever the neuroanatomical correlate of λ⊥ or λ || might be, our observation of similar effects of λ⊥ and λ || provides no further evidence regarding the cellular basis of these effects.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Further, parallel ADC was found to be positively correlated with axonal diameter, and negatively with axonal number (Schwartz et al, 2005). It should be noted that other tissue parameters, such as axon density and tortuosity, crossing fibres and tract geometry may also contribute to differences in λ⊥ and λ || (Beaulieu, 2009;Schwartz et al, 2005). Whatever the neuroanatomical correlate of λ⊥ or λ || might be, our observation of similar effects of λ⊥ and λ || provides no further evidence regarding the cellular basis of these effects.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, a study of the normal rat cervical spinal cord found that the perpendicular apparent diffusion coefficient (ADC), a measure similar to MD, was positively correlated with extracellular volume fraction and axonal spacing, and negatively correlated with axonal number and myelination. Further, parallel ADC was found to be positively correlated with axonal diameter, and negatively with axonal number (Schwartz et al, 2005). It should be noted that other tissue parameters, such as axon density and tortuosity, crossing fibres and tract geometry may also contribute to differences in λ⊥ and λ || (Beaulieu, 2009;Schwartz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if it were coupled with information on ECS and ICS volume fractions, new insights into axonal architecture can be gained such as an estimate of the axon count, an important parameter in determining function after spinal cord injury (Schwartz et al, 2005b) or quantification of axon loss, which would affect the ECS and ICS volume fractions, and demyelination, which would increase the displacement profile FWHM, both of which are hallmarks of spinal cord injury and a variety of WM diseases from multiple sclerosis to Alzheimer's disease (Budde et al, 2007;Horsfield and Jones, 2002). FWHM and zero-displacement probability have been observed to increase and decrease, respectively, in the presence of axon loss and demyelination (Assaf et al, 2002a), which we have also observed in ICS-weighted simulations of synthetic circular axons exhibiting only 10% axonal loss (data not shown).…”
Section: Discussion Estimating Mean Axon Diameter With Qsimentioning
confidence: 99%
“…Recent work has used DWI to investigate regional axon architecture (Schwartz et al, 2005a;Schwartz et al, 2005b). Schwartz et al performed ex vivo DWI of normal adult rat cervical spinal cords and computed transverse ADC (tADC) maps and longitudinal ADC (lADC) maps, i.e.…”
Section: Comparison To Conventional Diffusion Mri Techniquesmentioning
confidence: 99%